2013
DOI: 10.1002/humu.22485
|View full text |Cite
|
Sign up to set email alerts
|

NPHS2Mutations in Steroid-Resistant Nephrotic Syndrome: A Mutation Update and the Associated Phenotypic Spectrum

Abstract: Mutations in the NPHS2 gene encoding podocin are implicated in an autosomal-recessive form of nonsyndromic steroid-resistant nephrotic syndrome in both pediatric and adult patients. Patients with homozygous or compound heterozygous mutations commonly present with steroid-resistant nephrotic syndrome before the age of 6 years and rapidly progress to end-stage kidney disease with a very low prevalence of recurrence after renal transplantation. Here, we reviewed all the NPHS2 mutations published between October 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 79 publications
(112 reference statements)
1
53
0
3
Order By: Relevance
“…For instance, we have shown that whereas single-gene causes of SRNS were previously found in 26% of SRNS cases, 2 they were never detected in 120 cases with SSNS, 5 strongly suggesting that individuals with single-gene causes of SRNS will not respond to steroid treatment. 29 This finding has since been confirmed by another group 27 and was again confirmed for 185 individuals with SSNS in this study. Identification of the causative mutation may reveal that a potential therapy is available for some rare singlegene causes of SRNS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For instance, we have shown that whereas single-gene causes of SRNS were previously found in 26% of SRNS cases, 2 they were never detected in 120 cases with SSNS, 5 strongly suggesting that individuals with single-gene causes of SRNS will not respond to steroid treatment. 29 This finding has since been confirmed by another group 27 and was again confirmed for 185 individuals with SSNS in this study. Identification of the causative mutation may reveal that a potential therapy is available for some rare singlegene causes of SRNS.…”
Section: Discussionsupporting
confidence: 86%
“…The previously published founder alleles for NPHS2: Arg138Gln (European founder), 11 Pro118Leu (Turkish founder), 12 Val180Met (North African founder), 11 p.Arg138* (Israeli/ Arab founder), 11 Gly140Aspfs*41 (Southern European founder) 11 and Val260Glu (Comoros and the Sultanate of Oman founder) 12 were confirmed in our cohort as predominant in their regions of origin (Supplemental Figure 7). 27 We Figure 7). These findings will help establish genotypephenotype correlations in clinical settings of distinct locations around the world.…”
Section: Allelic Distribution In the 8 Largest Centersmentioning
confidence: 95%
“…Crumbs homolog 2 (CRB2) defects have been associated with steroid-resistant NS. NPHS2 mutations have been associated with steroid resistance (17, 18). …”
Section: Pathology Of Common Causes Of Ns In Childhoodmentioning
confidence: 99%
“…Pathogenic podocin mutations are responsible for the steroid-resistant nephrotic syndrome (SRNS-OMIM: 600995), which follows the autosomal recessive mode of inheritance. Podocin is a membrane-integral protein belonging to the stomatin family, and in the kidney it is exclusively localized at the cytoplasmic face of the SD, which bridges podocyte foot processes [19,20,21]. Saleem et al [22 ]showed that it co-localizes with nephrin and cytoskeletal actin while they provided evidence for its role in the foot process formation.…”
Section: Introductionmentioning
confidence: 99%